Climatic change of Bangladesh over a cycle of period 35 years (Journal of Bangladesh Academy of Sciences, 2015)
Bangladesh has been undergoing hazardous climatic changes. Monsoon is changing its pattern. Variations of temperature, humidity, rainfall are remarkable. The seasonal changes of Bangladesh such as the transition from winter to spring, summer to autumn in temperate zone, and from wet to dry in the tropics are remarkable to take into consideration. The climatic changes have great influence on the distribution of plants and animals and in the formation of soils through the weathering of geological materials and the decomposition or preservation of organic matter. Various weather parameters over a cycle were studied and determined the coefficient of variations to compare the past, present and future situation in Bangladesh. The frequency distribution and the shift in distribution of monsoon rainfall were determined and analyzed to show the trend of climate changes and their impact on environment. The important findings are the surface temperature rise by 0.60C and the rainfall in monsoon likely to be increased by 12% in the year 2030. However, the seasonal rainfall trend is decreasingJournal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 73-82, 2015